A review of naturally occurring radioactive elements in coastal regions of Bangladesh (Bangladesh Journal of Nuclear Agriculture, 2023)
Extensive and systematic study has been carried out globally to get a thorough understanding of the underlying dynamics of radionuclides in the environment. This study was aimed to examine the natural radioactivity level in coastal areas of Bangladesh by combining the main research carried out on environmental radioactivity, predominantly employing established nuclear methods and methodologies during the past. The concentrations of important radionuclides, including 226Ra, 232Th, 40K, 238U, and 235U, were measured in those investigations. Soil samples showed the highest concentration of 226Ra at Inani Beach, Cox's Bazar (21°8ʹ N latitude, 92°4ʹ E longitude), with a value of 61.66 Bqkg-1. On the other hand, Cox's Bazar Sea Beach has the lowest 226Ra concentration at 10.8 Bqkg-1. In contrast, Cox's Bazar had the highest 226Ra activity in the sand and silt samples (147.93 Bqkg-1), whereas Kuakata Sea Beach (21° 48ʹ N latitude and 90° 10ʹ E longitude) had the lowest (2.82 Bqkg-1). The research found that 226Th activity varied from 1085.99 Bqkg-1 to 27.4 Bqkg-1 in soil samples from Cox's Bazar Sea Beach. In Cox's Bazar, the sand and silt samples showed the highest 226Th activity at 1085.9 Bqkg-1. In contrast, Kuakata Sea Beach has the lowest radioactivity at 9.22 Bqkg-1. Soil samples showed that 40K content was highest at Inani Beach (21°13ʹ N latitude and 92°3ʹ E longitude), Cox's Bazar (1304.11 Bqkg-1) and lowest at Cox's Bazar Sea Beach (25.16 Bqkg-1). The sand and silt sample from Kuakata Sea Beach had the greatest 40K activity, measuring 852 Bqkg-1. However, the sample from Cox's Bazar Sea Beach had the lowest amount (21.9 Bqkg-1). Soil samples from Cox's Bazar Sea Beach showed 238U activity of 455.99 Bqkg-1 and 110.84 Bqkg-1, respectively. The highest 238U activity sand sample was found in Cox's Bazar, measuring 460.5 Bqkg-1. The Patenga region (22°14ʹ N  latitude and 91°47ʹ E longitude) in Chattogram has the lowest radioactive level, 45.2 Bqkg-1. The study's findings have been meticulously recorded as crucial foundational knowledge for forthcoming investigations on radionuclides in this coastal area. A comprehensive evaluation of prior published analyses of naturally occurring radioactive elements in the coastal regions of Bangladesh has shown that the level of activity is completely non-hazardous. The experimental areas' soils are ideal for a variety of agricultural and other purposes.Bangladesh J. Nuclear Agric, 37(2): 135-152, 2023